Anion Exchanger 1 Gene (AE1) Single Nucleotide Polymorphism (SNP) Analysis Among Malays With Distal Renal Tubular Acidosis (DRTA) And Southeast Asian Ovalocytosis (SAO) - Raman, Yamunah (2018)
Anion Exchanger 1 (AE1) encoding the erythroid and kidney isoforms of AE1 protein is located on chromosome 17. Distal renal tubular acidosis (dRTA) is characterized as its inability to acidify urine pH caused by AE1 polymorphisms. Southeast Asian Ovalocytosis (SAO) is a hereditary red blood cell abnormality caused by 27bp deletions in AE1. dRTA and SAO is highly prevalent in Southeast Asian countries. Polymorphism in AE1 is known to cause both SAO and dRTA associated with 27bp deletions which is still unclear.